Development of the Circuit Basketball Learning Model for Junior High School Students in Physical Education Learning - Siti Nur Izzah (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aimed to develop a Circuit Basketball learning model for seventh-grade junior high school students and examine its feasibility, practicality, and effectiveness in improving cognitive, affective, and psychomotor learning outcomes in physical education basketball learning activities. Methodology: This study employed a Research and Development (R&D) method based on the Borg and Gall model. Data were collected through observation sheets, questionnaires, interviews, documentation, and learning assessment sheets involving 12 students in small-group trials, 34 students in large-group trials, one basketball expert, and two physical education learning experts. Data were analyzed using descriptive quantitative and qualitative analysis techniques. Main Findings: The results showed that the Circuit Basketball learning model achieved a “very good” feasibility category with an average expert validation score of 89.6%. Small-group trials produced an average score of 80 in the “good” category, while large-group trials achieved an average score of 86 in the “very good” category. The model improved students’ participation, motivation, confidence, teamwork, and basketball basic skills during learning activities. Novelty/Originality of this study: The novelty of this study lies in the integration of basketball game modification and circuit training principles into a structured and student-centered learning model specifically designed for beginner-level junior high school students. The developed model combines technical skill practice, enjoyable movement activities, simplified rules, and modified facilities to create more effective and engaging basketball learning experiences.